The Effect of Zakat Collection, Company Age, and Company's Total Assets on Financial Performance of Sharia Banking in Indonesia 2019-2020 - Achmad Nur Iman; Raditya Sukmana; Alfath Shifa Ghifara; Akhmad Kusuma Wardhana (Economic Education and Entrepreneurship Journal, 2022)
This study aims to determine the relationship of the collection of Zakat, bank age, and total assets to the financial performance of Islamic banking in a sample of several Islamic banks in Indonesia in 2020 using multiple linear logistic regression test in the 2016-2020 period. The results show that company age and total assets of Islamic banks have a positive and significant effect on the spatial performance of Islamic banks. Meanwhile, what happened to the collection of zakat, the data showed that the collection of zakat of Islamic banks did not have a significant positive effect on the financial performance of Islamic banks. It is suspected that the large standard deviation of the zakat variable causes the first hypothesis to be unsupported. The existence of third party funds (DPK) is also suspected of having an effect on the unsupported first hypothesis.Keywords: Assets, Indonesia, Islamic Banks, ROA, Zakat.